Social media provides support and education for pregnant people when healthcare does not - Elissa Z. Faro; Donna A. Santillan; Meghan L. Funk; Kara Boeldt; Mark K. Santillan (Frontiers in Global Women's Health)
IntroductionThe use of social media for health-related reasons is growing, but there is a dearth of research on the mechanisms of support provided. Understanding how social media groups work could improve communications between providers and patients. Preeclampsia (PreE) is a hypertensive disease of pregnancy that has short- and long-term physical and psychosocial effects. The Preeclampsia, Eclampsia & HELLP Syndrome Survivors Global Support Network (PEHSS) Facebook group is an online, international, moderated support group that provides evidence-based information and community support. Our study aimed to (1) characterize the forms of social support and types of information sought and provided from the perspective of the group moderators and members, and (2) describe group members' experiences of patient care. We triangulated interview and survey findings to identify gaps in care, ultimately to inform in improvements in care delivery.MethodsWe began with 30–45-minute semi-structured interviews with PEHSS moderators exploring experiences and perceptions of membership; preliminary findings were member-checked with additional moderators. Interviews were analyzed using template and matrix analysis. Based on emergent themes, we conducted an online, validated patient experience survey with PEHSS members that was analyzed using descriptive statistics.ResultsEmotional and social support, mental health, resources and education, and personal health advocacy emerged as major themes in the 12 interviews. 1,148 PEHSS members responded to the survey. 68% of survey participants wanted to be more involved in the decisions about their care and treatment and over 30% felt they were not informed about danger signals post discharge while approximately half reported always feeling treated with respect and dignity while in the hospital. Geographic analysis showed differences in experiences of communication with providers within and outside the US.DiscussionThe triangulated results from interviews and surveys indicated a need for better communication with providers and the ability for patients to have more input on their care. The survey results indicate a global issue in providing support for people with hypertensive disorders of pregnancy during their hospitalization. The needs currently supported through communities on social media highlight opportunities to address critical gaps in care.